{2(х + у) - 3(х - у) = 3
{3(х + у) - 2(х - у) = 7
- - - - - - -
{2х + 2у - 3х + 3у = 3
{3х + 3у - 2х + 2у = 7
- - - - - - -
{5у - х = 3
{5у + х = 7
- - - - - - -
Вычтем из первого уравнения системы второе
-2х = -4
х = -4 : (-2)
х = 2
- - - - - - -
5у - 2 = 3 или 5у + 2 = 7
5у = 3 + 2 5у = 7 - 2
5у = 5 5у = 5
у = 5 : 5 у = 5 : 5
у = 1 у = 1
Вiдповiдь: (2; 1).
2) 12*12=144
3)2*2*2*2=16
4) 4*4*4=64
5)10*10*10=1000
1)3*3+4*4=25
2)3*3*3+2*2*2=35
3)26*26-(12*12*3+175)=69
4) 6*6*6-2*4*4*4-1*1*1=87
5) 15*15: (4*4-2*2*2)=28,125
6) 8*8*8:(4*4-2*2*2)=64